Architecture of hybrid mechatronic dosing and packing module of packaging machine based on qualitative analysis - Gavva, Oleksandr M.; Kryvoplias-Volodina, Liudmyla; Marynin, Andriy; Tokarchuk, Serhii; Blazhenko, Serhii; Volodin, Oleksandr (My University, 2023)
A qualitative analysis of the process of packaging liquid products (non-carbonated drinking water) using the example of a hybrid mechatronic dosing and packaging module was performed. The computer model of the mechatronic module is described by the basic operators of the Simulink program, taking into account the differential equations for changing the technological parameters of liquid dosing and the accepted initial and boundary conditions of the process. The modes of operation of the hybrid mechatronic dosing and packaging module are programmed using the driver. The boundary conditions of the process of formation and extrusion of the dose of the product are taken into account. The control system of the module is arranged on the principle of feedback and a sharp change in pressure in the portion receiver (from excess, within 3 bars to rarefaction up to –850 mbar). The analysis of individual stages of the dosing process is described, followed by the elaboration of accepted assumptions. During the tests of the computer model of the hybrid mechatronic dosing and packaging module, the accuracy of repetitions of dose formation was determined within ±0.22 % and 0.9 % of the set value of the dose mass of 50…200 ml. An experimental bench was designed, which could provide an opportunity to check the results obtained from the computer model. The research results would allow using digital control and measuring equipment to check the accuracy of dosing of the product from 50 ml to 200 ml. In the course of computer simulation, the effects of the given parameters of the dosing process on the accuracy of the product dose formation were determined, as well as the laws of the necessary distribution of compressed air pressure were formed to maintain the given productivity. The research results could make it possible to improve the designs of liquid product dosing modules and to determine the input parameters for field studies.

Виконано якісний аналіз процесу фасування рідких продуктів (негазованої питної води) на прикладі гібридного мехатронного дозувально-пакувального модуля. Комп'ютерна модель мехатронного модуля описана базовими операторами програми Simulink з урахуванням диференціальних рівнянь зміни технологічних параметрів дозування рідини та прийнятих початкових і граничних умов процесу. Режими роботи гібридного мехатронного модуля дозування та пакування програмуються за допомогою драйвера. При цьому враховуються граничні умови процесу формування і видавлювання дози продукту. Система управління модулем влаштована за принципом зворотного зв'язку і різкої зміни тиску в порційному приймачі (від надлишкового, в межах 3 бар до розрідження до -850 мбар). Описано аналіз окремих етапів процесу дозування з подальшим опрацюванням прийнятих припущень. Під час випробувань комп'ютерної моделі гібридного мехатронного дозувально-пакувального модуля визначено точність повторень формування дози в межах ±0,22 % та 0,9 % від заданого значення маси дози 50...200 мл. Розроблено експериментальний стенд, який може надати можливість перевірити результати, отримані на комп'ютерній моделі. Результати досліджень дозволять за допомогою цифрового контрольно-вимірювального обладнання перевірити точність дозування продукту від 50 мл до 200 мл. В ході комп'ютерного моделювання було визначено вплив заданих параметрів процесу дозування на точність формування дози продукту, а також сформовано закони необхідного розподілу тиску стисненого повітря для підтримки заданої продуктивності. Результати досліджень дозволять удосконалити конструкції модулів дозування рідких продуктів та визначити вхідні параметри для проведення натурних досліджень.
Keywords: кафедра мехатроніки та пакувальної техніки; кафедра машин і апаратів харчових та фармацевтичних виробництв; кафедра технологічного обладнання та комп’ютерних технологій проектування; dose formation; hybrid mechatronic module; dosing and packaging operation; feedback; dosing accuracy; формування дози; гібридний мехатронний модуль; дозування та пакування; зворотній зв'язок; точність дозування